The Decision Model for the Optimal Configuration Management of Knowledge Employees in Enterprises - Yang, Chunjiang; Yang, Yujiang; Tan, Xiuli (Informatica, 2018)
With the development of knowledge economy, the role of knowledge employees in enterprises has become larger and large and employees with rich knowledge have even been the tower of strength in the development of enterprises. Knowledge employees with strong autonomy and creativity have stronger self-awareness in daily work. Thus how to dispatch those knowledge employees and assign them to proper positions has been a problem that must be solved. To solve the problem of employee dispatch, this study proposed to optimize the configuration management of knowledge employees in enterprises using bacterial foraging algorithm, established the mathematical model based on the optimal configuration of knowledge employees, and made simulation experiments on the model. It was found that the method could effectively fulfill the optimal configuration of knowledge employees. It is a feasible method for employee dispatch in enterprises.